NBP reactions to changes in inflation and economic growth during the COVID–19 pandemic - Grabia, Tomasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2022)
The article aims to assess the monetary policy of the NBP during the coronavirus pandemic in the context of its proper response to changes in inflation and economic growth rates. The article puts forward a hypothesis according to which the NBP’s reactions in the form of interest rate changes during the pandemic were too late, triggering high galloping inflation in the first months of 2022. To verify it, we adopted comparative analyses of actual CPI and core inflation rates with the inflation target, as well as the NBP reference rate with hypothetical interest rates calculated on the basis of the Taylor rule modified for Poland. On the basis of these analyses the hypothesis was accepted.